Short-term and long-term effects of psychosocial factors on changes in medical adherence among patients with coronary heart disease - Fan, Yunge (Nanyang Technological University, 2022)
Coronary heart disease (CHD) is the global leading cause of mortality and disabilities, which is a chronic illness that often requires lifetime management. Although effective medical treatment has proved to successfully improve the prognoses and outcomes of patients with CHD, low adherence to medical treatment (e.g., taking prescribed medications and following recommended lifestyle behaviors) is still common among patients. Psychosocial factors, such as psychological distress and social support, are generally recognized as predictors of patients’ medical adherence. Previous research has suggested that adherence is more likely to fluctuate over time. However, few prior studies have focused on the fluctuation in medical adherence and there is a lack of systematic investigation on the specific change in trajectory of adherence over time in CHD patients. To fill in the research gaps, this longitudinal study examined the fluctuation in medical adherence and its specific change in trajectories over time among patients with CHD. Moreover, the influences of psychosocial factors, including psychological distress and social support, on change in medical adherence were investigated. At baseline, 255 CHD patients were recruited from those who participated in a community-based Heart Wellness Center at the Singapore Heart Foundation. Medical adherence was assessed at the baseline, 3, 6, 9, and 12 months. Meanwhile, psychological distress, including depression, loneliness, and perceived stress, and social support were measured at the baseline, 3, and 12 months. Among the 255 participants recruited at the baseline, 198, 188, 167, and 165 were followed-up at 3, 6, 9, and 12 months, respectively. The results were separately reported in three studies in this thesis. Study 1 aimed to investigate the dynamic nature of medical adherence and its specific change in trajectory over 12 months using latent growth curve (LGC) modeling. Three LGC models, including the no-change model, linear change model, and quadratic change model, were compared. The results showed that the quadratic change model fitted the data best, while the no-change model performed the worst on the model fit indices. As for the specific change in trajectory of medical adherence, there was a slight decrease over the first 6 months and followed by an increase from 6 to 12 months. In Study 2, we examined the relationship between changes in three different forms of psychological distress (i.e., depression, loneliness, and perceived stress) and the fluctuation in adherence at 3 months and 12 months. The results indicated that not only increase in depression, but also greater loneliness and perceived stress independently predicted decline in medical adherence over 12 months. More specifically, aggravated symptoms in depression at 3 months and 12 months predicted a decrease in medical adherence at the respective follow-ups. The increase in loneliness predicted a decline in medical adherence at 12 months but not at 3 months. Additionally, the increase in perceived stress at 3 months and 12 months predicted a decrease in adherence at the respective time points. Study 3 was designed to explore the influence of perceived social support on medical adherence. In addition to the direct effect of social support, this study also tested its buffering effect on the relationship between psychological distress (i.e., depression, loneliness, and perceived stress) and adherence. It was found that increase in social support contributed to an increase in adherence at both 3 months and 12 months. With respect to the buffering effect, the interactions between baseline social support and baseline psychological distress (i.e., depression, loneliness, and perceived stress) predicted adherence at baseline but not at follow-ups. Moreover, change in social support was not found to buffer the association between change in psychological distress (i.e., depression, loneliness, and perceived stress) and change in adherence over time. This study highlights the importance of continuously monitoring patients’ adherence to medical treatment and recommended lifestyle. In addition, the findings underline the necessity of tracking psychosocial factors, including various forms of psychological distress and perceived social support, over time for CHD patients to promote medical adherence and further improve disease prognosis. Psychosocial interventions to improve perceived social support and alleviate psychological distress are recommended to be provided on a continuous basis during the course of CHD rehabilitation.